Effect of some tillage methods and sowing dates on bulk density, soil moisture and sorghum yield in the rainfed areas of northern Gedarif , Gedarif State , Sudan - Elamin, Elwaleed M.; Omer, Mekki A. (Gezira Journal of Agricultural Science, 2017)
The study was carried out during three consecutive seasons (2005/06, 2006/07 and 2007/08) under rain-fed conditions, to investigate the effect of some tillage methods and sowing dates  of  sorghum ( Sorghum bicolor L. ) on soil moisture  content, bulk density and sorghum grain  yield  in  northern Gedarif area, at the pilot farm of the Faculty of Agricultural  and Environmental Sciences, University of  Gedarif, Gedarif, Sudan. The experiment was laid out in a split plot design with three replicates. Main plots were assigned to three tillage methods; which were:  Zero tillage (ZT), offset disc as post harvest tillage(PHT) and farmers practice which was  wide level disc (WLD) as control, while sub-plots were assigned  to two sowing dates  which were early sowing date (S1) and late sowing date (S2). Post-harvest tillage treatment (PHT) resulted in significantly higher soil moisture content in the three growing seasons  compared to the other two treatments. Combined analysis indicated that ZT resulted in  significantly higher soil bulk density  in comparison with WLD and PHT treatments  for the three depths. The 3-years average grain yield for PHT, WLD and ZT were 1113 kg/ha, 976 kg/ha and 885 kg/ha, respectively.  The respective increase in yield was  26% and 14%.                                                                                                                                                                              The study was carried out during three consecutive seasons (2005/06, 2006/07 and 2007/08) under rain-fed conditions, to investigate the effect of some tillage methods and sowing dates  of  sorghum ( Sorghum bicolor L. ) on soil moisture  content, bulk density and sorghum grain  yield  in  northern Gedarif area, at the pilot farm of the Faculty of Agricultural  and Environmental Sciences, University of  Gedarif, Gedarif, Sudan. The experiment was laid out in a split plot design with three replicates. Main plots were assigned to three tillage methods; which were:  Zero tillage (ZT), offset disc as post harvest tillage(PHT) and farmers practice which was  wide level disc (WLD) as control, while sub-plots were assigned  to two sowing dates  which were early sowing date (S1) and late sowing date (S2). Post-harvest tillage treatment (PHT) resulted in significantly higher soil moisture content in the three growing seasons  compared to the other two treatments. Combined analysis indicated that ZT resulted in  significantly higher soil bulk density  in comparison with WLD and PHT treatments  for the three depths. The 3-years average grain yield for PHT, WLD and ZT were 1113 kg/ha, 976 kg/ha and 885 kg/ha, respectively.  The respective increase in yield was  26% and 14%.